ANALISIS KEUNTUNGAN USAHA KERUPUK KULIT SAPI (Studi Kasus :Usaha Pengohan Kulit Sapi Pak Mukhtar Kecamatan Kota Juang Kabupaten Bireuen) - Suryani, Suryani; Yusdiana, Yusdiana (STOCK Peternakan, 2024)
This research was conducted in Meunasah Blang Village, Kota Juang District, Bireuen District, Province of Aceh. The location of the research was determined purposively (purposive) on the grounds that Meunasah Blang Village is the only village that produces cowhide crackers. The time of this research was conducted from January to February 2023. The purpose of this study was to determine the amount of income and the feasibility of the leather cracker business in Meunasah Blang Village, Kota juang District, Bireuen Regency. The research method used in this study is quantitative data obtained from observations, interviews and documentation, namely by observing directly to the location of the business of making skin crackers. Based on the results of research on the cowhide cracker business in Meunasah Blang Village, Kota Juang District, Bireuen Regency, it was found that the average revenue for the cowhide cracker business in Meunasah Blang Village, Juang City District, Bireuen Regency was IDR 6,000,000/month with a production cost of Rp. IDR 3,694,653/month. The production costs consist of fixed costs of IDR 876,653/month and variable costs of IDR 2,818,000/month. From the results of data analysis, it was found that the profit earned from the cowhide cracker business in Meunasah Blang Village, Kota Juang District, Bireuen Regency was IDR 2,305,347/month. Based on the calculation of business feasibility (R/C), namely the ratio of total revenue to total production costs which is greater than one, which has a ratio of 2.43, or 2.43 1, with a BEP price of IDR 33,531,741.04 and BEP Unit 1117.72 packs, it can be concluded that the cow skin cracker business is feasible to develop.